Antenatal findings and early postnatal outcomes in pregnancies with trisomy 21: a 10 year retrospective review at a tertiary centre. (17th August 2022) - Stott, Daniel; Dos Santos, Francois; Rodgers, Anna; Holgado, Elaine; Pandya, Pranav P.
Abstract: Objective: To examine the antenatal imaging features, intrapartum findings and early postpartum course of pregnancies with trisomy 21 (T21) at a tertiary hospital in the United Kingdom. Methods: Women with pregnancies diagnosed with T21 on antenatal or post‐mortem/postnatal karyotyping, from February 2010–2020. Outcome measures included antenatal imaging findings, fetal growth restriction (FGR), birthweight, mode of delivery and early neonatal outcomes. Results: 76 women were included. There were six intrauterine deaths and 70 livebirths. Thirty‐eight (50%) had an antenatal diagnosis and twenty‐five (33%) had a suspected diagnosis but declined further testing. The diagnosis was unanticipated in 13 (17%). Cardiac anomalies (35.5%) were the most common antenatal anomaly. Doppler abnormalities were apparent in 48/73 (68%). Eighteen (25.7%) had antenatal FGR. The majority were delivered by Caesarean section, and 21.4% of babies weighed <third percentile at delivery. Fifty‐eight (82%) were admitted to the neonatal unit. Forty‐three (61%) required respiratory support and fifty‐five (78%) needed naso‐gastric feeding or were nil by mouth. Mean PAPP‐A values were significantly lower in cases with abnormal Dopplers, FGR, congenital anomalies and birthweight <10 th percentile. Conclusions: T21 fetuses have high rates of placental insufficiency, FGR and Doppler abnormalities. Postnatally, most require respiratory and feeding support. Antenatal counselling should reflect these risks. Key points: What is already known about this topic? Well‐established screening protocols for trisomy 21. Evidence of higher rates of in‐utero death in affected pregnancies. Some evidence showing higher rates of placental insufficiency. What does this study add? We have shown high rates of placental insufficiency. T21 pregnancies complicated by growth restriction and structural anomalies have significantly lower PAPP‐A levels. Significant proportion (82%) of neonates with trisomy 21 require admission to the neonatal intensive care unit and the majority require feeding and respiratory support.